2017
DOI: 10.1073/pnas.1706286114
|View full text |Cite
|
Sign up to set email alerts
|

Infants possess an abstract expectation of ingroup support

Abstract: One pervasive facet of human interactions is the tendency to favor ingroups over outgroups. Remarkably, this tendency has been observed even when individuals are assigned to minimal groups based on arbitrary markers. Why is mere categorization into a minimal group sufficient to elicit some degree of ingroup favoritism? We consider several accounts that have been proposed in answer to this question and then test one particular account, which holds that ingroup favoritism reflects in part an abstract and early-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(124 citation statements)
references
References 55 publications
11
108
2
3
Order By: Relevance
“…While it is known that infants and young children are capable of distinguishing between arbitrary groups and can use that information in inferential judgments (Jin & Baillargeon, 2017), research on age-related changes in bias manifestation is somewhat mixed. While it is known that infants and young children are capable of distinguishing between arbitrary groups and can use that information in inferential judgments (Jin & Baillargeon, 2017), research on age-related changes in bias manifestation is somewhat mixed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is known that infants and young children are capable of distinguishing between arbitrary groups and can use that information in inferential judgments (Jin & Baillargeon, 2017), research on age-related changes in bias manifestation is somewhat mixed. While it is known that infants and young children are capable of distinguishing between arbitrary groups and can use that information in inferential judgments (Jin & Baillargeon, 2017), research on age-related changes in bias manifestation is somewhat mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Human beings have a natural proclivity to make distinctions between "us" and "them", which has survival value (Diesendruck, 2013), but is also a source of bias and prejudice. Group biases manifest early in development (Jin & Baillargeon, 2017), and carry with them expectations of behavior and constrain the possible actions individuals believe others will engage in (Rhodes & Chalik, 2013). Strongly held biases typically emerge around groups intimately tied to societally reinforced stereotypes, making them particularly susceptible to individual differences in life experiences (Hirschfeld, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity to social groups emerges early in life. Young children and even infants expect members of a social group to engage positively with one another (e.g., to help each other, share resources with each other) (Jin & Baillergeon, ; Misch, Over, & Carpenter, ; Rhodes & Chalik, ) and to share physical, behavioral and psychological attributes (e.g., Diesendruck & haLevi, ; Dunham, Baron, & Carey, ; Plötner, Over, Carpenter, & Tomasello, ; Powell & Spelke, ; Shutts, Pemberton‐Roben, & Spelke, ). Even though group members can share various attributes, however, different attributes are constrained by group membership in varying degrees.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that infants would perceive the wrongdoer and the victim, 2 group members of equal standing, to be entitled to an equal share of the toys, and hence that they would detect a fairness transgression when the wrongdoer took both toys, leaving none for the victim. Finally, there is also evidence that infants aged 12 to 17 mo possess an abstract expectation of ingroup support: For example, individuals in a group are expected to care for each other by refraining from unprovoked harm and by providing assistance when needed (47)(48)(49)(50). This suggested that infants would also perceive an ingroup-support transgression in our events and would be particularly sensitive to the plight of the victim, who was treated unfairly by a member of her own group.…”
Section: The Present Researchmentioning
confidence: 97%